COMPARISON OF ANATOMICAL INFORMATION OF COLUMNA VERTEBRAE CERVICAL IN 15 TO 20-DEGREE RIGHT POSTERIOR OBLIQUE PROJECTION - Zuzilla; T.Mohd Yoshandi; Danil Hulmansyah (LPPM STIKes Awal Bros Pekanbaru, 2021)
Columna cervical vertebrae are a type of long bone that occurs on the back of the head. One of the radiological examinations most frequently performed in the hospital is the examination of the right posterior oblique projection cervical vertebrae (RPO). However, to see the cervical vertebrae column radiograph that is more optimal for cases of HNP, fractures, fissures, root symdrome. with a variation of the angle of 15 ° and 20 ° cranially. To find out which method is the most informative to display the right posterior oblique (RPO) projection with an angle of 15 ° and 20 ° cranially. This research is a type of quantitative research with statistical expansion. This research uses phantom. The research was conducted at the STIKes Awal Bros Pekanbaru in August 2020. The vertebral column results were used well, namely at an angle of 15 ° with clearly visible vertebral foramen, clearly visible intervertebral disc, visible C4 - C7, spinous process, clearly visible intervertebral disc.